Pursuing the Complexity of Alzheimer's Disease: Discovery of Fluoren-9-Amines as Selective Butyrylcholinesterase Inhibitors and N-Methyl-d-Aspartate Receptor Antagonists - Konecny, Jan; Misiachna, Anna; Hrabinova, Martina; Pulkrábková, Lenka; Benkova, Marketa; Prchal, Lukas; Kucera, Tomas; Kobrlová, Tereza; Finger, Vladimir; Kolcheva, Marharyta; Kortus, Stepan; Jun, Daniel; et al. (Biomolecules, 2020)
Alzheimer's disease (AD) is a complex disorder with unknown etiology. Currently, only symptomatic therapy of AD is available, comprising cholinesterase inhibitors and N-methyl-d-aspartate (NMDA) receptor antagonists. Drugs targeting only one pathological condition have generated only limited efficacy. Thus, combining two or more therapeutic interventions into one molecule is believed to provide higher benefit for the treatment of AD. In the presented study, we designed, synthesized, and biologically evaluated 15 novel fluoren-9-amine derivatives. The in silico prediction suggested both the oral availability and permeation through the blood-brain barrier (BBB). An initial assessment of the biological profile included determination of the cholinesterase inhibition and NMDA receptor antagonism at the GluN1/GluN2A and GluN1/GluN2B subunits, along with a low cytotoxicity profile in the CHO-K1 cell line. Interestingly, compounds revealed a selective butyrylcholinesterase (BChE) inhibition pattern with antagonistic activity on the NMDARs. Their interaction with butyrylcholinesterase was elucidated by studying enzyme kinetics for compound 3c in tandem with the in silico docking simulation. The docking study showed the interaction of the tricyclic core of new derivatives with Trp82 within the anionic site of the enzyme in a similar way as the template drug tacrine. From the kinetic analysis, it is apparent that 3c is a competitive inhibitor of BChE.
Keywords: CHO buňky; fluoreny; Humans; hematoencefalická bariéra; Computer Simulation; Blood-Brain Barrier; Receptors, N-Methyl-D-Aspartate; lidé; Alzheimer Disease; zvířata; Alzheimerova nemoc; CHO Cells; cholinesterasové inhibitory; Cricetulus; receptory N-methyl-D-aspartátu; počítačová simulace; butyrylcholinesterasa; Fluorenes; inhibitory enzymů; Animals; Butyrylcholinesterase; Enzyme Inhibitors; Cholinesterase Inhibitors